The Effect of Ecolinguistics on Dhamir Misuse in Arabic Conversation at Islamic Boarding Schools - Annisa Eriska Wulandari Wima; Maskud Maskud; Syamsul Anam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study investigates the influence of ecolinguistic factors on the misuse of ḍamīr (pronouns) in Arabic conversations among students in Islamic boarding schools (pesantren). Employing a qualitative descriptive method, data were collected through interviews, observations, and linguistic error analysis. The findings indicate that environmental elements—such as the habitual use of local languages and the limited exposure to Arabic in daily interactions—significantly contribute to errors in the use of ḍamīr. Among the types of pronouns, ḍamīr muttaṣil exhibited the highest frequency of errors (60%), followed by ḍamīr munfaṣil (30%) and ḍamīr mustatir (10%). These errors occurred more frequently in informal contexts, underscoring the role of situational language use. The study highlights the critical role of an immersive and supportive language environment in fostering accurate Arabic usage. Its implications are relevant for the refinement of Arabic language instruction in pesantren, offering pedagogical recommendations to enhance language competence through ecolinguistically responsive teaching strategies.